From Consuming to Producing: Otaku as free Labor in the Japanese Anime and Manga Industry - Rohmah, Nidar Lutfiyatur; Iskandar, Kurniawaty (RA Journal of Applied Research, 2022)
This study aims to analyze the role of otaku in the Japanese anime industry, where otaku is not only consumers but also producers in the Japanese anime industry. Furthermore, this study also analyzes how otaku work as free labor in the Japanese anime industry. In looking at the existing phenomena, this study uses the theory of free labor and database consumption to analyze the phenomenon more deeply. This study uses a qualitative method. The data used are primary data taken through in-depth interviews with two sources (otaku) and supported by secondary data from articles and related research. The results show that manga and anime fans (otaku) often form social interactions between fandoms and produce activities to acquire or expand the works they consume. Otaku is not only consumers of manga or anime but also often have derivative products, such as doujinshi, AMV, and others, from the manga and anime they consume. By creating derivative works, otaku act as free laborers who work not for material purposes but for satisfaction purposes (hobbies).